Mobile Phones and Social Behavior among Millennials - future teachers - Tomaz Bratina (University of Maribor Press, 2019)
The increased number of mobile devices changes the communication habits and lifestyle. Consequently, social norms and values change. Millennials define new patterns in social behavior, communication, interpersonal relationships, and interaction. Simultaneous e-communication in the presence of another person and lack or rejection of face-to-face contact are just the most common kinds of social behavior. Appropriate social behavior when using a mobile phone is crucial for Millennial future teachers, who will be teaching Millennials. The results of this study show current and changing patterns of social behavior induced by the use of mobile phones among future teachers. Ignorance, simultaneous e-communication and replacement of face-to-face contact are all present. These results also reveal the desire for close contact with a beloved person. The extensive daily use of mobile phones for about 5 hours or more is the second undesired finding among future teachers.